Associations of chemical tracers and faecal indicator bacteria in a tropical urban catchment - Ekklesia, Eveline (2015)
Surface water contamination by human faecal wastes is a widespread hazard for human health. Faecal indicator bacteria (FIB) are the most widely used indicators to assess surface water quality but are less-human-specific and have the potential to survive longer and/or occur naturally in tropical areas. In this study, 13 wastewater chemicals (chloride, boron, orthosphophate, detergents as methylene blue active substances, cholesterol, cholestanol, coprostanol, diethylhexyl phthalate, caffeine, acetaminophen, ibuprofen, sucralose and saccharin) were investigated in order to evaluate tracers for human faecal and sewage contamination in tropical urban catchments. Surface water samples were collected at an hourly interval from sampling locations with distinct major land uses: high-density residential, low-density residential, commercial and industrial. Measured concentrations were analysed to investigate the association among indicators and tracers for each land-use category. Better correlations were found between different indicators and tracers in each land-use dataset than in the dataset for all land uses, which shows that land use is an important determinant of drain water quality. Data were further segregated based on the hourly FIB concentrations. There were better correlations between FIB and chemical tracers when FIB concentrations were higher. Therefore, sampling programs must be designed carefully to take the time of sampling and land use into account in order to effectively assess human faecal and sewage contamination in urban catchments. FIB is recommended as the first tier in assessment of surface water quality impairment and chemical tracers as the second tier. Acetaminophen and coprostanol are recommended as chemical tracers for high-density residential areas, while chloride, coprostanol and caffeine are recommended for low-density residential areas.